Frequency-domain approach to the causal nexus between domestic and international economic policy uncertainties and equity returns of G20 countries - Moses Dumayiri; Imhotep Paul Alagidede; Yakubu Awudu Sare (Cogent Economics & Finance, 2024)
While uncertainty shocks affect equity markets at various investment horizons, knowledge about the causal effects of uncertainty and equity markets in the frequency domain is scant among the Group of Twenty (G20) countries regarded as systemically important economies. This paper explores the causal relations between domestic and international (US) economic policy uncertainties (EPU) and equity market returns of G20 countries. By employing the frequency-domain causality test, with monthly data spanning January 1997 to June 2021, we reach the following conclusions: 1) irrespective of the frequency, there is more support for the equity-leading hypothesis, implying that domestic stock market volatility contributes to increasing domestic policy uncertainty, as policymakers occasionally have to alter policies in reaction to elevated stock market volatility; 2) the causality between policy uncertainty (whether domestic or international) and equity returns is sensitive to heterogeneous investment decisions and policy uncertainty across horizons in most of our sample; 3) International (US) policy uncertainty has a domineering causal effect in predicting domestic equity returns, relative to domestic policy uncertainty in the short run of about 2.5 months or less. Therefore, the prediction that stock prices fall following government policy announcements is not always supported since countries are different. The G20 forum comprises major economies representing a significant part of global economic activity and playing a crucial role in global economic governance. Therefore, decisions taken at the G20 forum should represent important news for financial markets with potential effects on asset prices. Moreover, market participants in these markets react to and value information relating to policy developments heterogeneously based on the differences in the formation of their beliefs, preferences, risk tolerance abilities, information assimilation, liquidity needs, investment objectives and institutional constraints. However, previous literature has mainly assumed homogeneity in agents' behaviour, resulting in a dearth of knowledge about the causal effects of uncertainty and equity markets in the frequency domain among the G20 countries. Therefore, this paper analyses the dependence between domestic and international policy uncertainties and equity market returns of G20 countries in the frequency domain. The results show that the dependence patterns between EPU and equity returns tend to vary across different investment horizons in support of the predictions of the fractal market hypothesis. Nonetheless, the stock price leading hypothesis is more dominant regardless of the investment horizon, suggesting that frequent interventions by policymakers to dampen market volatility during periods of high policy uncertainty may exacerbate the uncertainty. Moreover, International (US) policy uncertainty has a domineering causal effect in predicting domestic equity returns relative to domestic policy uncertainty in the short run of about 2.5 months or less. By assuming the homogeneity of market participants, this study offers a nuanced understanding of causal relationships across different time horizons. The findings challenge conventional wisdom about the impact of policy uncertainties on equity markets, revealing complex and heterogeneous effects across countries. These results have significant implications for policymakers, investors, and financial institutions by providing a more accurate and granular perspective on risk management, portfolio allocation, and policy design.
Keywords: 330; Economic policy uncertainty; frequency-domain causality approach; G20 equity markets; equity-leading hypothesis; uncertainty-leading hypothesis; fractal market hypothesis